2019
DOI: 10.1155/2019/4253846
|View full text |Cite
|
Sign up to set email alerts
|

In a Rat Model of Acute Liver Failure, Icaritin Improved the Therapeutic Effect of Mesenchymal Stem Cells by Activation of the Hepatocyte Growth Factor/c-Met Pathway

Abstract: Acute liver failure (ALF) is a serious life-threatening condition. Mesenchymal stem cells (MSCs) may be an effective treatment for this condition and a good alternative to liver transplantation. Icaritin (ICT) is an active ingredient of the genus Epimedium, a traditional Chinese medicine, with the potential to enhance the proliferation of MSCs. The purpose of this study was to explore whether ICT increased the therapeutic effects of MSCs and explore its underlying mechanisms. For in vivo experiments, a rat ALF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In vivo, the expressions of HGF in each MSCs group differed and this was consistent with the trend of the effects of stem cells. Previous studies have reported that HGF can promote the directional migration of a variety of cells [13,14]. Moreover, HGF is closely related to the vascular endothelium function [29].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In vivo, the expressions of HGF in each MSCs group differed and this was consistent with the trend of the effects of stem cells. Previous studies have reported that HGF can promote the directional migration of a variety of cells [13,14]. Moreover, HGF is closely related to the vascular endothelium function [29].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have reported that HGF plays a major role in promoting migration in many tumors [11,12]. Other studies have con rmed that HGF promotes the directional migration of MSCs [13,14]. Roggia et al con rmed HGF enhanced the differentiation of embryonic stem cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…A diversity of studies recently has focused on combination therapy with MSCs and other molecules or modalities to diminish ALF. Meanwhile, co-administration of MSCs with Icaritin, a well-known ingredient isolated from traditional Chinese medicine, resulted in promising outcomes in vivo [ 131 ]. Indeed, MSCs co-cultured with Icaritin improved survival, reduced serum levels of AST and ALT, and elicited histological variations in liver tissue more potently than MSCs alone.…”
Section: Mscs In Alf (Animal Studies)mentioning
confidence: 99%
“…Indeed, MSCs co-cultured with Icaritin improved survival, reduced serum levels of AST and ALT, and elicited histological variations in liver tissue more potently than MSCs alone. Importantly, the up-regulation of HGF/c-Met by Icaritin was found to be involved in MSCs-triggered antiapoptotic influences on hepatocytes, reflecting the potential of herbal extracts to promote MSC-mediated therapeutic impacts [ 131 ]. The addition of the granulocyte colony-stimulating factor (G-CSF) to UCB-MSCs also improved survival and reduced ROS and pro-inflammatory cytokines expressions in ALF murine model [ 132 ].…”
Section: Mscs In Alf (Animal Studies)mentioning
confidence: 99%
“…Icaritin (ICT) is an active ingredient of the genus Epimedium , a traditional Chinese medicine, with the potential to enhance the proliferation of MSCs. Lu et al [ 37 ]found out that MSCs increased the survival rate of acute liver failure rats and reduced liver damage. MSCs cocultured with ICT exerted a greater therapeutic effect than MSCs alone.…”
Section: Mechanism Of Bmscs In Liver Cirrhosismentioning
confidence: 99%